ANALYSIS OF THE PRESENCE OF INTERNAL CAVITIES IN PIN-TYPE POLYMERIC INSULATORS UNDER POLLUTION - Leite Neto, Antonio Francisco; da Costa, Edson Guedes; Dias, Bruno Albuquerque; de Melo, João Victor Jales (Seven Editora, 2025)
This paper presents a study of the electric field in pin type insulators under the influence of an internal cavity. Polymeric insulators 15 kV were modeled with the aid of technical design software. Computational simulations to obtain the electric field were performed using COMSOL Multiphysics. The simulated cavity inside the insulator has spherical and elliptical geometry, with different values for its diameter. The position of the internal defect was varied from a region near the cable to a region near the hardware. For each simulated case, three levels of pollution were applied to the surface of the insulator, also considering the case in which it is intact. The results obtained for the case in which the insulator is intact does not present large variations in the electric field in the internal region. With the presence of a cavity, the electric field distortions in the cavity region assumed high values, surpassing in some cases the value of the dielectric strength of atmospheric air. The most critical defect detected was for elliptical geometry, whose electric field values were higher than the spherical case. DOI: https://doi.org/10.56238/sevened2025.029-104